A recepção do projeto de H. T. Buckle para a fundação científica da história pelo jovem Dilthey como o primeiro momento de sua tese sobre a necessidade de uma psicologia descritiva e analítica no sistema das ciências do espírito - Silva, Guilherme José Santini da (2020)
The Dilthey’s project for a Critique of Historical Reason was first mentioned by him in 1860, during his formative years in Berlin. This project is conceived in the midst of a preexisting debate on the task of the scientific foundation of historical knowledge. In this debate, Dilthey's project stands out for one of his theses, the one that defends a new Psychology, according to the descriptive and analytical method, as a condition for the success of such a task. Our hypothesis is that this thesis came to be tackled in his critical reception of Henry Thomas Buckle's project, that is contained in History of Civilization in England, book destined to the same task. Buckle's project starts from the premise of the unity of the behavior of natural and human phenomena and scientific and methodological monism. In 1862 in a reviews intitled History and Science, the young Dilthey opposes Buckle, accusing him of ignoring the specificity of historical material and its respective method; but, in addition, Dilthey argues that the English positivist would not have gone further into the investigation of the "inner core of the historical spirit’s activity". The defense of the need for this investigation will unfold only later, when Dilthey argues in favor of a new Psychology, applied to the facts of consciousness, as they are experienced in internal experience. Our primary objective will be to expose the context in which Dilthey points out, against Buckle, the need for this investigation of the "inner core of the historical spirit’s activity"; and how he later matures the thesis about it. For that, the debate in which the History and Science text is inscribed will be reconstructed. It will thus be seen which theses of other authors were in dialogue. However, upon receiving Buckle's project, the young Dilthey took into account the theses of Auguste Comte and Johan Gustav Droysen, authors who had already exposed their projects to the scientific foundation of history according to different premises. Consequently, it will become explicit why the task of a philosophical-scientific foundation of History culminates, in Dilthey, in the search for a new concept of subjectivity that, in his view, only a new Psychology, descriptive and analytical, could explain